The influence of consumptive behavior, transaction convenience, and promotions on the decision of ukts students in using spaylater - Sunarto, Misael Sabatian; Raharjo, Lyna (ProBisnis : Jurnal Manajemen, 2024)
The study investigates consumptive behavior among college students, focusing on the influence of promotions and transaction convenience on decision-making, specifically regarding the use of SPaylater. Data was collected through questionnaires and analyzed using multiple linear regression. Results indicate that consumptive behavior significantly affects students' decisions to use SPaylater, with a regression coefficient of 0.220 and a t-value of 2.122 (p < 0.05). Transaction convenience, however, showed insignificant influence, with a regression coefficient of 0.149 and a t-value of 0.805 (p > 0.05). Promotions, particularly those offered by Shopee, significantly influence students' decisions, with a regression coefficient of 0.690 and a t-value of 2.478 (p < 0.05). This highlights the importance of attractive promotions in influencing students' choices. Overall, the study underscores the significance of understanding consumer behavior and promotional strategies in shaping students' decisions regarding SPaylater usage.